Association of SLC2A9 genotype with phenotypic variability of serum urate in pre-menopausal women - Topless, Ruth K.; Flynn, Tanya J.; Cadzow, Murray; Stamp, Lisa K.; Dalbeth, Nicola; Black, Michael A.; Merriman, Tony R. (Frontiers in Genetics, 2015)
The SLC2A9 gene, that encodes a renal uric acid reuptake transporter, has genetic variants that explain 3% of variance in urate levels. There are previous reports of non-additive interaction between SLC2A9 genotype and environmental factors which influence urate control. Therefore our aim was to further investigate the general phenomenon that such non-additive interactions contribute to genotype-specific association with variance at SLC2A9. Data from 14135 European individuals were used in this analysis. The measure of variance was derived from a ranked inverse normal transformation of residuals obtained by regressing known urate-influencing factors (sex, age and BMI) against urate. Variant rs6449173 showed the most significant effect on serum urate variance at SLC2A9 (P = 7.9x10-14), which was maintained after accounting for the effect on average serum urate levels (P=0.022). Noting the stronger effect in a sub-cohort that consisted of pre-menopausal women and younger men, the participants were stratified into males and pre-menopausal and post-menopausal women. This revealed a strong effect on variance in pre-menopausal women (P=3.7x10-5) with a weak effect in post-menopausal women (P=0.032) and no effect in men (P=0.22). The T-allele of rs6449173, which associates with increased urate levels, was associated with the greater variance in urate. There was a non-additive interaction between rs6449173 genotype and female gender in control of serum urate levels that was driven by a greater increase in urate levels associated with the T-allele in women. Female hormones, and/or other factors they influence or are associated with (such as iron levels, temperature, testosterone) interact with SLC2A9 genotype in women to determine urate levels. The association of SLC2A9 with greater variance in pre-menopausal women may reflect the cyclical changes resulting from menstruation.